Creation of entangled atomic states by an analogue of the Dynamical Casimir effect. (12th October 2018) - Lange, K; Peise, J; Lücke, B; Gruber, T; Sala, A; Polls, A; Ertmer, W; Juliá-Díaz, B; Santos, L; Klempt, C
Abstract: If the boundary conditions of the quantum vacuum are changed in time, quantum field theory predicts that real, observable particles can be created in the initially empty modes. Here, we realize this effect by changing the boundary conditions of a spinor Bose–Einstein condensate, which yields a population of initially unoccupied spatial and spin excitations. We prove that the excitations are created as entangled pairs by certifying continuous-variable entanglement within the many-particle output state.